Hydrocortisone and Ascorbic Acid Synergistically Prevent and Repair Lipopolysaccharide-Induced Pulmonary Endothelial Barrier Dysfunction - Barabutis, Nektarios (Chest, 2017)
BACKGROUND: Sepsis refers to the dysregulated host immune response elicited by microbial infections resulting in life-threatening organ dysfunction. Sepsis represents a medical challenge, since it is associated with a rate of death as high as 60%. Septic shock is strongly associated with vascular dysfunction and elevated pulmonary capillary permeability. We recently reported that the combination of hydrocortisone (HC), ascorbic acid (vitC), and thiamine dramatically improves outcomes and reduces mortality in patients with sepsis. In the present study, we provide experimental evidence in support of the hypothesis that the combination of HC and vitC enhances endothelial barrier function. METHODS: Human lung microvascular endothelial cells were exposed to lipopolysaccharide (LPS) in the absence or presence of HC and vitC. RESULTS: LPS alone induced profound hyperpermeability, as reflected in decreased values of transendothelial electrical resistance. vitC alone did not exhibit barrier enhancement properties nor did it affect the LPS-induced hyperpermeability. Similarly, HC alone exhibited only a minor barrier-enhancing and protective effect. Conversely, the combination of HC and vitC, either as before or after treatment, dramatically reversed the LPS-induced barrier dysfunction. The barrier-protective effects of HC and vitC were associated with reversal of LPS-induced p53 and phosphorylated cofilin downregulation and LPS-induced RhoA activation and myosin light chain phosphorylation. CONCLUSIONS: These data provide a novel mechanism of endothelial barrier protection and suggest one possible pathway that may contribute to the therapeutic effects of HC and vitC in patients with sepsis.